Digital Transformation and Technology Adoption Patterns Among Generation Z: Impact on information literacy and social behavior - Azzahroh, Nabila Harumnike (Maliki Interdisciplinary Journal, 2026)
Digital transformation has significantly changed the lives of Generation Z, who have grown up alongside the rapid development of the internet, social media, and digital technologies. This study aims to analyze how digital transformation shapes Generation Z’s technology adaptation patterns and its impact on information literacy and social behavior. The research employs a qualitative descriptive approach through a literature review using various academic sources, including scientific journals, books, scholarly articles, and previous research findings. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that Generation Z possesses a high level of technological adaptability, enabling them to utilize various digital platforms for learning, communication, and skill development. Digital transformation has also improved access to information and expanded social networks. However, these developments have generated several challenges, including technological dependency, exposure to misinformation and hoaxes, and a decline in the quality of face-to-face interactions. Therefore, strengthening information literacy is essential to help Generation Z critically evaluate, manage, and use information responsibly. Enhanced information literacy can support the effective and ethical use of technology while fostering healthier social interactions in the digital era.